Sequential Cursed Equilibrium - Cohen, Shani; Li, Shengwu (American Economic Review, 2026)
We propose an extensive-form solution concept, with players who neglect information from hypothetical events but make inferences from observed events. Our concept modifies cursed equilibrium (Eyster and Rabin 2005) and allows that players can be cursed about endogenous information. (JEL C73, D44, D71, D81, D83, D91)